Study about Electrical Appliance Usage and Electricity Consumption Pattern at Household Level - Lakshmi , V. Vijaya; Paul , M. Milcah (Research Developments in Science and Technology Vol. 1, 2022)
This study was undertaken to study the type of appliances used by consumers and also the electricity consumption and expenditure patterns in the residences in the sub-urban households. Electricity is one of the important secondary fuels used by all the consumers in the world. In the suburban suburbs of Hyderabad, Telangana State, an exploratory study method was employed on 30 randomly selected families. The data was gathered using a standardised interview schedule. Frequency, percentage, and correlation were used to analyse the data. The results showed that the respondent households used a greater number of miscellaneous appliances as compared to the other appliances used for different purposes like cooking, heating, cooling, laundry etc. Majority of the households stood in the low consumption level (0 - 250 units/month) of electricity, classified as per the study. Majority spent Rs. 1 – Rs. 1000/- month as an expenditure for the electricity consumed, which was considered as a low level of expenditure. Consumers must be properly educated and made aware of the significance of reducing energy usage and increasing energy conservation. To encourage customers and households to use less electricity, the government should implement various projects that recognise or compensate households that consume electricity appropriately and on a regular basis.